Brain Magnetic Resonance Imaging Findings Fail to Suspect Fabry Disease in Young Patients With an Acute Cerebrovascular Event. Issue 6 (June 2015) - Fazekas, Franz; Enzinger, Christian; Schmidt, Reinhold; Grittner, Ulrike; Giese, Anne-Katrin; Hennerici, Michael G.; Huber, Roman; Jungehulsing, Gerhard J.; Kaps, Manfred; Kessler, Christof; Martus, Peter; Putaala, Jukka; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Fabry disease (FD) may cause stroke and is reportedly associated with typical brain findings on magnetic resonance imaging (MRI). In a large group of young patients with an acute cerebrovascular event, we wanted to test whether brain MRI findings can serve to suggest the presence of FD. Methods— The Stroke in Young Fabry Patients (SIFAP 1) study prospectively collected clinical, laboratory, and radiological data of 5023 patients (18–55 years) with an acute cerebrovascular event. Their MRI was interpreted centrally and blinded to all other information. Biochemical findings and genetic testing served to diagnose FD in 45 (0.9%) patients. We compared the imaging findings between FD and non-FD patients in patients with at least a T2-weighted MRI of good quality. Results— A total of 3203 (63.8%) patients had the required MRI data set. Among those were 34 patients with a diagnosis of FD (1.1%), which was definite in 21 and probable in 13 cases. The median age of patients with FD was slightly lower (45 versus 46 years) and women prevailed (70.6% versus 40.7%; P<0.001). Presence or extent of white matter hyperintensities, infarct localization, vertebrobasilar artery dilatation, T1-signal hyperintensity of the pulvinar thalami, or any other MRI finding did not distinguish patients with FD from non-FD cerebrovascular event patients. Pulvinar hyperintensity was not present in a single patient with FD but seen in 6 non-FD patients. Conclusions— Brain MRI findings cannot serve to suspect FD in young patients presenting with an acute cerebrovascular event. This deserves consideration in the search for possible causes of young patients with stroke. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00414583.